2020
DOI: 10.1002/prp2.643
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic effects of mirabegron are mediated primarily by β3‐adrenoceptors

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Our data emphasize that mirabegron ( 82 ), a drug in current clinical use, increases lipolysis and thermogenesis in human brown/beige adipocytes specifically through activation of the β 3 -AR. These data are in accordance with our clinical studies where we observed that acute mirabegron treatment increases FFA and energy expenditure ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 51%
“…Our data emphasize that mirabegron ( 82 ), a drug in current clinical use, increases lipolysis and thermogenesis in human brown/beige adipocytes specifically through activation of the β 3 -AR. These data are in accordance with our clinical studies where we observed that acute mirabegron treatment increases FFA and energy expenditure ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 51%
“…Isoprenaline has a reported pKi of 5.3–3.4 for the rat β 3 ‐adrenoceptor (Alexander, Christopoulos, et al, 2019a; Popp et al, 2004), concentrations well beyond that required for full dilation of the cremaster muscle artery, perhaps suggesting why isoprenaline did not appear to activate β 3 ‐adrenoceptor in the current study. β 3 ‐adrenoceptor‐mediated isoprenaline responses at lower concentrations (pEC 50 7–8) have been observed in a variety of cell and tissue types (Arch & Kaumann, 1993; Dehvari et al, 2020; Hutchinson et al, 2001), although reported pEC 50 values for arterial relaxation are around 5 (Brawley et al, 2000; Flacco et al, 2013; Riedel et al, 2019). Relative receptor expression levels may also contribute to the lack of β 3 ‐adrenoceptor‐mediated isoprenaline effects in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Michel & Korstanje, 2016). Other possible clinical applications of β 3 -adrenoceptor ligands are emerging (Arioglu-Inan et al, 2019;Dehvari et al, 2018Dehvari et al, , 2020, particularly in relation to the cardiovascular system. Current clinical trials are investigating the efficacy of mirabegron as an inotropic agent in heart failure (BEAT-HF; Bundgaard et al, 2017), in preventing hypertension-induced ventricular hypertrophy and diastolic dysfunction (Beta3-LVH;Pouleur et al, 2018) and in relieving heart failure-related pulmonary hypertension (SPHERE-HF; Garcia-Lunar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we did not observe this effect in white adipocytes. Although the adrenergic pathway is fully functional in white adipocytes leading to cAMP production, PKA activation, and lipolysis [ 41 ], it fails to induce glucose uptake in white adipocytes and WAT [ 34 , 60 ]. However, in contrast to GLUT4, the basal expression levels of GLUT1 in white adipocytes are known to be higher than in brown [ 22 ], in agreement with our data.…”
Section: Discussionmentioning
confidence: 99%